Alphavirus E1 Glycoprotein-Liposome-Nucleic Acid Complexes Protect Mice from Lethal Challenge with Multiple Alphaviruses. Issue 4 (May 2015) - Rico, A; Phillips, A; Schountz, T; Toth, A; Jarvis, D; Powers, A; Olson, K
Abstract : Alphaviruses are globally distributed, mosquito borne pathogens that cause death and disease in vertebrates, including humans. Therapeutics to combat alphaviral disease are non-existant and only a handful of IND status vaccines are available. Of the available vaccines most are associated with a poor immunological response and a high rate of reactivity, and none protects against more than a single alphavirus species. We designed and tested novel alphavirus vaccines comprised of the E1 glycoproteins of western equine encephalitis virus (WEEV) or Venezuelan equine encephalitis virus (VEEV). Immunization with cationic lipid nucleic acid complexes (CLNCs) and alphavirus E1ecto mixture (lipid-antigen-nucleic acid complexes:LANACs) provided significant protection in mice challenged with either WEEV, VEEV or eastern equine encephalitis virus (EEEV) regardless of challenge route. LANAC immunized mice mount a strong humoral immune response lacking neutralizing antibody. Passive transfer of immune sera from LANAC immunized mice to non-immunized mice confers protection to challenge, indicating that non-neutralizing antibody is sufficient for protection. In summary, our LANAC vaccine has both therapeutic and prophylactic potential and is able to offer protection against distinct alphavirus species irrespective of the route of infection.